Utilization and efficacy of internet-based eHealth technology in gastroenterology: a systematic review. (April 2014) - Knowles, Simon R.; Mikocka-Walus, Antonina
Abstract Objective. While there have been several reviews exploring the outcomes of various eHealth studies, none have been gastroenterology-specific. This paper aims to evaluate the research conducted within gastroenterology which utilizes internet-based eHealth technology to promote physical and psychological well-being. Material and methods. A systematic literature review of internet-based eHealth interventions involving gastroenterological cohorts was conducted. Searched databases included: EbSCOhost Medline, CINAHL, and PsycINFO. Inclusion criteria were studies reporting on eHealth interventions (both to manage mental health problems and somatic symptoms) in gastroenterology, with no time restrictions. Exclusion criteria were non-experimental studies, or studies using only email as primary eHealth method, and studies in language other than English. Results. A total of 17 papers were identified; seven studies evaluated the efficacy of a psychologically oriented intervention (additional two provided follow-up analyses exploring the original published data) and eight studies evaluated disease management programs for patients with either irritable bowel syndrome, inflammatory bowel disease (IBD) or celiac disease. Overall, psychological eHealth interventions were associated with significant reductions in bowel symptoms and improvement in quality of life (QoL) that tended to continue up to 12 months follow up. The eHealth disease management was shown to generally improve QoL, adherence, knowledge about the disease, and reduce healthcare costs in IBD, although the studies were associated with various methodological problems, and thus, this observation should be confirmed in well-designed interventional studies. Conclusions. Based on the evidence to date, eHealth internet-based technology is a promising tool that can be utilized to both promote and enhance gastrointestinal disease management and mental health.